A Global Perspective on Testing Infants Online: Introducing ManyBabies-AtHome - Zaadnoordijk, Lorijn; Buckler, Helen; Cusack, Rhodri; Tsuji, Sho; Bergmann, Christina (Frontiers in Psychology, 2021)
Online testing holds great promise for infant scientists. It could increase participant diversity, improve reproducibility and collaborative possibilities, and reduce costs for researchers and participants. However, despite the rise of platforms and participant databases, little work has been done to overcome the challenges of making this approach available to researchers across the world. In this paper, we elaborate on the benefits of online infant testing from a global perspective and identify challenges for the international community that have been outside of the scope of previous literature. Furthermore, we introduce ManyBabies-AtHome, an international, multi-lab collaboration that is actively working to facilitate practical and technical aspects of online testing as well as address ethical concerns regarding data storage and protection, and cross-cultural variation. The ultimate goal of this collaboration is to improve the method of testing infants online and make it globally available.